2018
DOI: 10.1002/ange.201710100
|View full text |Cite
|
Sign up to set email alerts
|

Addition of H2 Across a Cobalt–Phosphorus Bond

Abstract: Addition of H 2 across the cobalt-phosphorus bond of (PPP)CoPMe 3 (3)isdemonstrated, where PPP is amonoanionic diphosphine pincer ligand with ac entral N-heterocyclic phosphido (NHP À )d onor.T he chlorophosphine Co II complex (PP Cl P)CoCl 2 (2)c an be generated through coordination of the chlorophosphine ligand (PP Cl P, 1)t oC oCl 2 . Subsequent reduction of 2 with KC 8 in the presence of PMe 3 generates (PPP)CoPMe 3 (3), in whichb oth the phosphorus and cobalt centers have been reduced. The addition of 1at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
(129 reference statements)
1
16
0
Order By: Relevance
“…Stoichiometric, MLC-assisted H2-activation facilitated by functional PPP and PCP pincer ligands. [115][116][117][118][119] A rapidly growing structural and functional variety of cooperating pincer ligands with many different cooperating groups were subjected to stoichiometric bond activation reactions and some proved suitable for catalysis. For example, Thomas and coworkers described the 1,2-addition of dihydrogen across a covalent Co-P-bond (Scheme 5).…”
Section: Metal-ligand Cooperativity (Mlc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Stoichiometric, MLC-assisted H2-activation facilitated by functional PPP and PCP pincer ligands. [115][116][117][118][119] A rapidly growing structural and functional variety of cooperating pincer ligands with many different cooperating groups were subjected to stoichiometric bond activation reactions and some proved suitable for catalysis. For example, Thomas and coworkers described the 1,2-addition of dihydrogen across a covalent Co-P-bond (Scheme 5).…”
Section: Metal-ligand Cooperativity (Mlc)mentioning
confidence: 99%
“…For example, Thomas and coworkers described the 1,2-addition of dihydrogen across a covalent Co-P-bond (Scheme 5). 115 Gutsulyak et al reported 1,2-addition of E-H bonds (E = H, NH2, OH, OCH3, CCPh, NHC(O)Ph, SiPh3) at a nickel carbene PCP pincer complex, [116][117][118][119] and Caulton and coworkers the 1,2-addition of dihydrogen along the Ni-N moiety of a cationic amido pincer Ni(II) complex (Scheme 6). 120 The bimetallic Ni(I)/Ni(I) PBP pincer complex Ni-6a was reported by Peters to undergo reversible MLC-assisted addition of dihydrogen (Scheme 6) but is inactive in olefin hydrogenation.…”
Section: Metal-ligand Cooperativity (Mlc)mentioning
confidence: 99%
“…Many of the most successful cobalt hydroboration catalysts take advantage of the stability and rigidity imparted by tridentate pincer ligands. , We turn our attention herein to a (PPP) − pincer ligand that incorporates an N-heterocyclic phosphido (NHP – ) moiety in the central donor position flanked by two diarylphosphine side arms . We have previously demonstrated that the tridentate (PPP) − pincer ligand can engage in metal–ligand cooperativity, through either bifunctional substrate activation across the metal-P bond or ligand-assisted redox processes. …”
Section: Introductionmentioning
confidence: 99%
“…Given that heavier tetrelene ligands can also act as strong electron-donating ligands, efforts have been made to develop novel pincer-type tetrelene ligands and to utilize them in combination with transition metals for various catalytic transformations. However, so far, they are limited to ECE or ENE systems (E = Si, Ge), and only very recently were the first phosphine-functionalized germylene and stannylene ligands and their applications reported. Given that polydentate carbene ligands and their polymetallic complexes often feature interesting properties such as photoluminescent behavior, we were interested in substituting the carbene carbon atom by its heavier analogues and explore the properties of such compounds. Thereby, we used a PNHNHP pro-ligand developed by Thomas and coworkers (pictured in Scheme ), whose synthesis is straightforward, feasible on a multigram scale, and has been extensively investigated. …”
Section: Introductionmentioning
confidence: 99%